Suppression of sloshing in floating roof tank by multi dynamic absorber - Nobuyuki KOBAYASHI; Tatsunori YOSHINO; Tomoya YORIKI (Nihon Kikai Gakkai ronbunshu, 2015)
This article presents a multi dynamic absorber for suppressing liquid sloshing in a floating roof tank. The presented multi dynamic absorber uses U-tubes set on the floating roof. Many seismic damages on floating roof tanks by the sloshing of the contained liquid in the tank due to long periodic components of earthquake were reported. Since the natural period of sloshing varies according to the liquid height, robustness for parameters variances such as natural period is required for the sloshing suppression device to obtain a good performance. From this point of view, a multi dynamic absorber is developed instead of the single dynamic absorber which is sensitive to the parameter variance. A multi degree of freedom mechanical model for sloshing of the contained liquid and the presented multi dynamic absorber on the floating roof of the tank is derived to design the optimal tuning and optimal damping for parameters of the multi dynamic absorber and to evaluate the sloshing suppression performance. Numerical simulations on two kinds of actual size floating roof tank are conducted to examine seismic response of the present device as well as the transfer function characteristics. As the result the presented multi dynamic absorber is effective to suppress the sloshing of the floating roof.